Metformin and glucose starvation decrease the migratory ability of hepatocellular carcinoma cells: targeting AMPK activation to control migration - Ferretti, Anabela (2019)
Hepatocellular carcinoma (HCC) is a highly metastatic cancer with very poor prognosis. AMP activated kinase (AMPK) constitutes a candidate to inhibit HCC progression. First, AMPK is downregulated in HCC. Second, glucose starvation induces apoptosis in HCC cells via AMPK. Correspondingly, metformin activates AMPK and inhibits HCC cell proliferation. Nevertheless, the effect of AMPK activation on HCC cell invasiveness remains elusive. Here, migration/invasion was studied in HCC cells exposed to metformin and glucose starvation. Cell viability, proliferation and differentiation, as well as AMPK and PKA activation were analyzed. In addition, invasiveness in mutants of the AMPKα activation loop was assessed. Metformin decreased cell migration, invasion and epithelial-mesenchymal transition, and interference with AMPKα expression avoided metformin actions. Those antitumor effects were potentiated by glucose deprivation. Metformin activated AMPK at the same time that inhibited PKA, and both effects were enhanced by glucose starvation. Given that AMPKα(S173) phosphorylation by PKA decreases AMPK activation, we hypothesized that the reduction of PKA inhibitory effect by metformin could explain the increased antitumor effects observed. Supporting this, in AMPK activating conditions, cell migration/invasion was further impaired in AMPKα(S173C) mutant cells. Metformin emerges as a strong inhibitor of migration/invasion in HCC cells, and glucose restriction potentiates this effect.